2007
DOI: 10.1186/1477-7827-5-16
|View full text |Cite
|
Sign up to set email alerts
|

Distinct phospholipase A2 enzymes regulate prostaglandin E2 and F2alpha production by bovine endometrial epithelial cells

Abstract: Background: The rate-limiting step in prostaglandin (PG) biosynthesis is catalyzed by phospholipase A2 (PLA2) enzymes which hydrolyze arachidonic acid from membrane phospholipids. Despite their importance in uterine PG production, little is known concerning the specific PLA2 enzymes that regulate arachidonic acid liberation in the uterine endometrium. The objectives of this study were to evaluate the expression and activities of calcium-independent Group VI and Group IVC PLA2 (PLA2G6 and PLA2G4C) and calcium-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
3
7

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(61 citation statements)
references
References 45 publications
3
47
3
7
Order By: Relevance
“…This is in contrast to observed IFNT effects described in vitro (Asselin et al 1997a, 1997c, Parent et al 2002, Emond et al 2004, Tithof et al 2007, Godkin et al 2008. In addition, the release of all PG examined is strikingly concomitant, making it likely that the general rather than the specific synthases account for the vast increase in PG.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…This is in contrast to observed IFNT effects described in vitro (Asselin et al 1997a, 1997c, Parent et al 2002, Emond et al 2004, Tithof et al 2007, Godkin et al 2008. In addition, the release of all PG examined is strikingly concomitant, making it likely that the general rather than the specific synthases account for the vast increase in PG.…”
Section: Discussioncontrasting
confidence: 52%
“…Moreover, it has been discussed that the relative production of PGE 2 and PGF 2a may be more important than the absolute levels of individual-secreted PG, in the choice between embryo implantation and resumption of the estrous cycle (Asselin et al 1997a). IFNT has been made responsible for the reduced production of PGF 2a relative to PGE 2 evidenced by numerous in vitro studies (Asselin et al 1997a, 1997c, Parent et al 2002, Emond et al 2004, Tithof et al 2007, Godkin et al 2008. However, we find clear evidence that there is no difference in PGF 2a /PGE 2 ratio between cyclic and pregnant uteri in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Prostaglandins are produced from the common precursor AA, which is liberated from cell membranes by phospholipase A2 (PLA2) enzymes. The type of prostaglandin produced may depend on the PLA2 enzyme that is stimulated, where the PLA2 group 6 enzyme is associated with PGF accumulation, and PLA2 group 4C enzyme is associated with PGE accumulation (Tithof et al 2007). A predominant release of luteoprotective PGE following an E. coli infection of the uterus may mediate the prolonged luteal phases that are associated with bovine endometritis (Mateus et al 2003, Herath et al 2009.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, IFNT appeared to negatively influence the expression of PGFS, PLA2G6 and PGDH mRNA as there were fewer transcripts in the gravid compared with the nongravid (with less exposure to IFNT) horns. PGFS expression is reportedly downregulated in response to IFNT in bovine endometrium as is PLA2G6 activity, a phospholipase that catalyses the rate-limiting step in prostaglandin biosynthesis by hydrolysing arachidonic acid from membrane lipids (Tithof et al 2007). PGDH converts PGE 2 and PGF 2a to their inactive metabolites (PGEM and PGFM, respectively) and although Arosh et al (2004) described PGDH protein expression as unaffected by IFNT, they subsequently reported that mRNA and protein expression were not directly related during the oestrous cycle (Parent et al 2006).…”
Section: Evaluation Of the Bovine Uterine Environmentmentioning
confidence: 99%